2012
DOI: 10.1044/1058-0360(2011/11-0009)
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Experience in the Perception of Phonetic Detail in Children’s Speech: A Comparison Between Speech-Language Pathologists and Clinically Untrained Listeners

Abstract: Purpose This study examined whether experienced speech-language pathologists differ from inexperienced people in their perception of phonetic detail in children's speech. Method Convenience samples comprising 21 experienced speech-language pathologist and 21 inexperienced listeners participated in a series of tasks in which they made visual-analog scale (VAS) ratings of children's natural productions of target /s/-/θ/, /t/-/k/, and /d/-/ɡ/ in word-initial position. Listeners rated the perception distance bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 37 publications
5
62
2
1
Order By: Relevance
“…To quantify the impact of cooling on speech quality for all recorded sound files, we used an online crowdsourcing approach adapted from a recently validated method (McAllister Byun et al, 2015), in which each vocalization was rated on a visual analog scale (VAS) (Munson et al, 2012) from 0 (‘Extremely degraded’) to 1 (‘Typical/Normal’). Each subject’s sound files were evaluated by 20.4 ±1.0 online participants.…”
Section: Resultsmentioning
confidence: 99%
“…To quantify the impact of cooling on speech quality for all recorded sound files, we used an online crowdsourcing approach adapted from a recently validated method (McAllister Byun et al, 2015), in which each vocalization was rated on a visual analog scale (VAS) (Munson et al, 2012) from 0 (‘Extremely degraded’) to 1 (‘Typical/Normal’). Each subject’s sound files were evaluated by 20.4 ±1.0 online participants.…”
Section: Resultsmentioning
confidence: 99%
“…There were substantial individual differences in the extent to which responses were biased toward the /s/ end of the scale. Previous studies have found that naïve listeners, like those in this study, have a tendency to label sounds /s/ rather than /θ/ (Munson et al, 2012). This was true in this data set.…”
Section: Resultsmentioning
confidence: 47%
“…VAS has also been used to study adults’ perception of children’s speech. In one such procedure, Munson, Johnson, and Edwards (2012) presented participants with a horizontal line with endpoints anchored with the text “the ‘s’ sound” at one end and “the ‘th’ sound” at the other end. Listeners were presented with children’s productions of target /s/ and target /θ/ and were asked to use a mouse to click a point on the line where they perceived that a given sound production fell along the continuum.…”
mentioning
confidence: 99%
“…This interpretation is also supported by some research on adult speech perception. Munson, Johnson, and Edwards (2012) found that highly trained speech-language pathologists perceive children’s speech more categorically than do phonetically untrained listeners.…”
Section: Gradiency In Speech Perceptionmentioning
confidence: 98%
“…Our speculation about how listeners might perceive the productions analyzed by Macken and Bartonis based on the results of numerous studies that elicit continuous ratings of children’s productions of sounds (Julien & Munson, 2012; McAllister Byun, Halpin, & Harel, 2015; Munson & Brinkman, 2004; Munson, Johnson, & Edwards, 2012; Munson, Schellinger, Edwards, Beckman, & Meyer, 2010; Strömbergsson, Savli, & House, 2015). These studies have shown that listeners are capable of providing continuous ratings of children’s productions, provided that the productions themselves vary continuously in how closely they resemble canonical productions of sounds.…”
Section: The Auditory-perceptual Assessment Of (Not-so-)covert Contrastmentioning
confidence: 99%